Analysis of Views on the Origin of the Word Sufism (on the Basis of Foreign and Uzbek Researches) - Abdumuminovich, Ismoilov Kakhramonjon (European Journal of Life Safety and Stability (2660-9630), 2023)
This article compares the opinions and views of some Uzbek and foreign scholars regarding the origin of the words Sufi and Sufism. It lists about ten meanings of the word Sufism, which repeat each other and sometimes complete.